ENHANCING ELEMENTARY SCHOOL STUDENTS’ UNDERSTANDING OF BASIC MATHEMATICAL CONCEPTS - Maureen Joanna Finny (CV. Fahr Publishing, 2025)
This study aims to strengthen elementary students’ conceptual understanding of basic mathematical concepts through an integrated instructional framework that combines concrete and virtual manipulatives, culturally contextualized learning tasks, and teacher-focused pedagogical content knowledge development. Using a library-based research method, the study systematically collected, evaluated, and synthesized empirical findings from the last five years to construct a theoretically grounded and evidence-based model for enhancing conceptual learning. The reviewed studies demonstrate that multimodal manipulatives significantly support students’ ability to form relational mathematical understanding, leading to higher post-test scores, improved retention, and better transfer to new contexts. Additionally, the analysis highlights that teacher conceptual pedagogical knowledge plays a critical mediating role, as classrooms led by well-prepared teachers show deeper mathematical discourse, reduced misconceptions, and more meaningful engagement. The novelty of this study lies in its dual-path approach, which simultaneously targets student learning through representational scaffolding and teacher learning through concept-focused professional development—an integration rarely addressed in early-grade mathematics research. Furthermore, the cultural embedding of mathematical tasks offers a contextually relevant contribution that responds to global calls for inclusive and locally meaningful mathematics instruction. Overall, the study proposes a comprehensive and scalable instructional model that can be adapted across diverse educational settings. In conclusion, the synthesis reveals that combining multimodal manipulatives, culturally responsive design, and strengthened teacher knowledge provides a powerful foundation for improving early numeracy and fostering long-term conceptual understanding in elementary mathematics.